Real-World Use of Topical Ruxolitinib in Vitiligo: Retrospective Cross-Sectional Mixed Methods Infodemiology Study of the r/Vitiligo Subreddit - Kirchberger, Michael Constantin; Berking, Carola; Eisenried, Andreas (Journal of Medical Internet Research, 2025)
Background: Vitiligo significantly impairs quality of life. Topical ruxolitinib is a novel Janus kinase inhibitor approved for nonsegmental vitiligo, but real-world patient experiences, particularly regarding efficacy, side effects, and access challenges following approval, are not fully captured by clinical trials. Online patient forums like Reddit offer valuable insights into these aspects. Objective: This study analyzed discussions on the r/Vitiligo subreddit regarding topical ruxolitinib to understand real-world patient experiences, perceived treatment success, side effects, access barriers, and overall sentiment. Methods: We conducted a retrospective, cross-sectional infodemiology study of posts and comments mentioning ruxolitinib or Opzelura on r/Vitiligo between January 2022 and December 2024. After filtering and preprocessing, 2950 entries were analyzed. Computational linguistics (all-MiniLM-L6-v2), including sentence-transformer embeddings for semisupervised topic classification into therapy success, side effects, insurance and cost, and off-topic, were used. Valence Aware Dictionary and Sentiment Reasoner (−1 to +1) for sentiment analysis was assessed. Temporal trends were analyzed; model performance was validated manually against blinded manual annotation of 500 entries. Representative qualitative data were reviewed. Results: Discussions increased following regulatory approvals. Therapy success was the largest cluster (entries: 1765/2950, 59.83%; 95% CI 58.1 to 61.6) with positive sentiment (mean score 0.473, 95% CI 0.46 to 0.48), frequently describing facial repigmentation and adjunctive use with phototherapy. Users reported encouraging hair repigmentation within treated areas and success even on vitiligo spots present for over 20 years, while noting that areas like hands and feet were particularly treatment-resistant. The side effects cluster (entries: 558/2950, 18.91%; 95% CI 17.5 to 20.3) had negative sentiment (mean score −0.110, 95% CI −0.14 to 0.07), frequently mentioning application-site acne, fatigue, and panic attacks or anemia. The insurance and cost cluster (entries: 491/2950, 16.64%; 95% CI 15.3 to 18.0) had positive sentiment (mean score 0.349, 95% CI 0.31 to 0.39), dominated by discussions on high costs and access difficulties, alongside strategies like co-pay programs but also noting insurance denials. Manual model validation showed substantial agreement (accuracy 88.4%, 95% CI 86 to 91; F1-score 0.893, 95% CI 0.865 to 0.918; Cohen κ 0.801, 95% CI 0.760 to 0.840). Conclusions: Real-world Reddit narratives broadly corroborate clinical trial efficacy signals, particularly facial repigmentation and utility alongside phototherapy, while highlighting practical barriers including frequent application-site acne and cost or insurance friction. These findings have direct clinical and policy implications: clinicians can proactively counsel about the expected benefit on facial areas, monitor and manage acne or irritation, and discuss combination with phototherapy; practices and payers can mitigate access delays using before authorization templates and co-pay assistance. Social media infodemiology thus complements pharmacovigilance and health services research by quantifying patient-reported outcomes and surfacing access issues at scale, informing patient counseling and coverage decisions in routine care.
CRIS-Team Scopus Importer:2025-10-31
Keywords: digital epidemiology; infodemiology; Reddit; ruxolitinib; vitiligo